Abundance and importance of petrological type 1 chondritic material. (7th November 2021) - Russell, Sara S.; Suttle, M. D.; King, A. J.
Abstract: We review the mineralogy, petrology, and abundance of petrological type 1 extraterrestrial material. Such material has been completely altered by aqueous processing on its parent bodies. As well as the four meteorite groups that contain type 1 members (CI, CM, CR, and CY), we summarize data from the 2019 fall Flensburg and a recent reanalysis of the "meteorite" Bench Crater found on the Moon, along with fine‐grained micrometeorites, interplanetary dust particles, and xenoliths in meteorites. Type 1 materials exhibit a remarkably high diversity of alteration conditions (temperature, water‐to‐rock [W/R] ratios, and fluid composition) and starting mineralogy. Type 1 material comprises a significant component of the modern extraterrestrial flux to the Earth and was likely common throughout the solar system during the whole course of its history, pointing to both widespread accretion with ices and heating of parent bodies. Type 1 materials are composed predominantly of various phyllosilicates, carbonates, sulfides, and magnetite. Some type 1 materials appear to be part of a "CM clan" typified by serpentine‐rich phyllosilicate compositions and an oxygen isotope composition that falls in the 16 O‐rich part of the CM field. Others span a wide range in δ 18 O (>30‰) and fall on or above the terrestrial fractionation line (+ve Δ 17 O). Positive Δ 17 O values are unusual for carbonaceous meteorites but are relatively common in type 1 materials. The wide variation in oxygen isotopes, as well as in textures, mineralogy, and bulk chemistry, points to multiple parent bodies that may originate in the inner and/or outer solar system. Cometary materials, or transition objects such as Main Belt comets or type D asteroids, are likely the source of much of the type 1 materials on Earth but relating them to specific parents requires more study.